Processos autocíclicos e alocíclicos afetando os registros da paleoflora da foz do rio Jucuruçu, litoral sul da Bahia, durante os últimos 1000 anos - MORAES, Caio Alves de (Universidade Federal do Pará, 2019)
The vegetation holocenic history along the southern Bahia littoral is characterized by establishment, expansion and contraction phases of mangroves. This vegetation dynamics is mainly associated to climate change and to relative sea level oscillations. However, punctually and in a smaller time scales, for example, during the last 1000 years, other processes inherent to the sedimentary dynamics of depositional environment, termed autocyclic processes, are controlling the pollen assembly along stratigraphic profiles formed by active channels followed by its abandonment. Based on sedimentary features, pollen grains, isotopes (δ13C, δ15N C/N) and radiocarbon dating of sedimentary organic matter from two cores (PR-11 and PR-12) sampled from an abandoned meander and a tidal flat in the mouth of the Jucuruçu river, is proposed a model for evolution of a tidal channel surrounded by wetlands. The core PR-11, with 1.48 meters depth, was sampled from a mangrove zone, with a maximum age of 678 cal yr BP. The PR-12 was collected from a várzea vegetation, approximately 2.7 km from the current shoreline with 1.92 meters depth and, maximum age of 680 cal yr BP. The data present two facies associations: (A) Tidal channel, represented by massive sand deposits (facies Sm); cross-stratified sand (Scs) and facies flaser heterolithic bedding (Hf) and (B) Tidal plain, represented by facies wavy heterolithic bedding (Hw), lenticular heterolithic bedding (Hl), massive mud (Mm) and massive sand (Sm). The pollen data reveals that the facies association (A) presents absence of pollen grains of mangroves. It may have been caused be an intense activity of sediments reworking of channel margins and sediment deposition with pollen grains sourced from vegetation units not necessarily from the study site. In the top of the studied succession, in association facies (B), is possible to identify the establishment and expansion of mangroves in the newly formed tidal flat (PR-11) or lake (PR-12). Regarding the core PR-12, it is marked by channel abandonment. The reduced interaction between fluvial discharge and tidal waves have caused the infilling of mud sediments, and a highest potential for organic matter preservation. It provided conditions for the mangrove development and pollen preservation. In the case of PR-11, the tidal channel migration have caused the development of a tidal flat, which have favored the mangrove expansion. These depositional environments, favorable to the formation of mangroves, can be partially or completely modified by the natural dynamics of tidal channels and estuarine channels, which are under the influence of changes of sedimentary fluvial contribution on the shore and littoral drift processes along the coast associated with tides, waves and currents. These results were compared with some data from one core sampled 23 km upstream of Jucuruçu River that also indicated the presence of mangroves on tidal flat with estuarine organic matter during the early and middle Holocene, followed by herbaceous vegetation on a fluvial plain with organic matter sourced from freshwater during the late Holocene (Fontes, 2015). In this case, the sea level fluctuations and climate change were the main driving forces controlling the wetlands dynamics at the mouth of this river during the Holocene, characterizing an allocyclic process. However, considering the stratigraphic sequences of the analyzed cores in this master's work (PR-11 and PR-12), such sedimentary sequences associated with changes in vegetation and sources of organic matter are related to the infilling processes of coastal depressions, mainly marked by active channels, abandoned channels and tidal flats. Therefore, in a small time scale of coastal vegetation changes are not necessarily directly associated with sea-level and climate change (allocyclic processes). On the other hand, processes associated to the sedimentary dynamics of the depositional environment (autocyclic processes) must have controlled pollen assembly along the studied stratigraphic profiles.